O novo mundo do trabalho no cinema: a precarização da vida - Ferreira, Ivo Júnior Celestino (2019)
In the last third of the twentienth century, due to the structural crisis of capital, the world of labour has undergone significant changes and the central tendency of this movement has been the precariousness of work conditions in a global scope. Having a theoretical basis of Marxism and social psychology of work, the present work aims to apprehend the impacts of the structural precariousness of labour in the lives of working class individuals from the analysis of of some cinematographic works, seeking to identify the way in which these works have managed to capture the determinations of the new world of labour, in particular the phenomenon of precariousness of life. For this, we started from the ideas about art as a way of knowing reality, developed by the Hungarian philosopher Georg Lukács. The works selected for analysis were: Mondays in the Sun (2002), by Fernando León de Aranoa; Two days, one night (2014), by the Dardenne brothers and I, Daniel Blake (2016), by Ken Loach. For the analysis, we used the critical method of Antonio Candido, each piece being analyzed individually and then try to point out the convergences and divergences between them. The conclusions we reached indicate that the new cinema of labour has proved fruitful in apprehending, through aesthetic means, the determinations of the new world of labour and the precariousness of life, thus bringing important contributions so that we can understand the main contradictions and challenges of our historical time.